Improvement of stages of adaptation and ex vitro pre-growing of red raspberry (Rubus idaeus L.) plants - Akimova Svetlana; Palamarchuk Diana; Makarov Sergey; Marchenko Lyudmyla; Soloviev Alexander (BIO Web of Conferences)
At the adaptation stage, a new multicomponent microbial concentrate obtained by fermentation of substrate from a mixture of peat, humus and compost by bifidobacteria was used for the first time. The microbial preparation is rich in BAS (probiotics, enzymes, amino acids, etc.), due to which it activates plant immunity and improves plant establishment, growth and development. The influence of different modifications of Revitalize liquid preparation (marka U - universal; marka Ya - for berry crops) in preparation of red raspberry microplants for the stage of adaptation to non-sterile conditions was studied. The work demonstrated the positive effect of Revitalize liquid marka Ya at the stage of adaptation for a single treatment with exogenous treatment. At the stage of pre-growing, the effectiveness of a single treatment with fertilization and a double treatment with mixed feeding was revealed.